Tacrolimus-eluting stent with biodegradable polymer is more effective than sirolimus- and everolimus-eluting stent in rabbit iliac artery restenosis model - Park, Dae Sung; Park, Jun-Kyu; Jeong, Myung Ho; Bae, In-Ho; Lee, So-Youn; Jang, Eun Jae; Lim, Kyung-Seob; Kim, Jong Min; Kim, Jung Ha; Hyun, Dae Young; Jeong, Yun Ah; Kim, Hyun Kuk; et al. (Macromolecular research, 2015)
Drug-eluting stents, which are widely used in percutaneous coronary intervention, are fabricated with various considerations, such as drugs, design, polymers, and coating techniques. The aim of this study was to compare tacrolimus-eluting stents (TES), sirolimus-eluting stents (SES) and everolimus-eluting stents (EES) under identical conditions. Poly(lactic- co -glycolic acid) (PLGA) biodegradable polymer was used to coat bare metal stents (Chonnam National University Hospital Stent, CNUH Stent) with the drugs in all fabricating procedures with an ultrasonic stent-coating machine. Surface morphologies of the stents were investigated by scanning electron microscopy. The effect of drugs released from stents on rat smooth muscle and human umbilical vein endothelial cells was examined by MTT assay. The stents were implanted in rabbit iliac arteries randomly, with either TES (n=10), SES (n=10), or EES (n=10). After six weeks of implantation, the stents were isolated and subjected to histopathological analysis. Cell viability decreased in a dose-dependent manner. The surface morphologies of the stents showed a smooth and uniform shape. The release patterns of the stents showed similar profiles over 30 days. There were no significant differences in the injury score, internal elastic lamina, lumenal area, neointimal area, percent area stenosis, and inflammation score among the three groups. However, there was a significant difference in the fibrin score (0.6±0.44 in the TES, vs . 0.8±0.48 in the SES, vs . 0.8±0.61 in the EES, n=10, p <0.05). This study showed that tacrolimus was not inferior to sirolimus (SRL) and everolimus (EVL). Moreover, tacrolimus (TCL) is more effective in decreasing the fibrin score. Therefore, tacrolimus can be a useful alternative drug for fabricating drug-eluting stents.